2011
DOI: 10.1007/s11626-011-9469-5
|View full text |Cite
|
Sign up to set email alerts
|

Efforts to develop a cultured sponge cell line: revisiting an intractable problem

Abstract: Residents of the marine environment, sponges (Porifera) have the ability to produce organic compounds known as secondary metabolites, which are not directly involved in the normal growth, development, or reproduction of an organism. Because of their sessile nature, the production of these bioactive compounds has been interpreted as a functional adaptation to serve in an important survival role as a means to counter various environmental stress factors such as predation, overgrowth by fouling organisms, or comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 23 publications
0
28
0
3
Order By: Relevance
“…In recent years, sponge dissociation experiments have largely been aimed at obtaining cell cultures for the production of bioactive compounds (Pomponi & Willoughby ; Grasela et al. ). These primary cultures are not usually a single cell type.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, sponge dissociation experiments have largely been aimed at obtaining cell cultures for the production of bioactive compounds (Pomponi & Willoughby ; Grasela et al. ). These primary cultures are not usually a single cell type.…”
Section: Discussionmentioning
confidence: 99%
“…Scientists have substantially increased their efforts to develop culture techniques for marine sponges, which include in situ aquaculture (reviewed by [68]) and ex situ culture approaches, such as aquarium culture, primmorphs and cell cultures (reviewed by [67,69]). While sea-based culture techniques (Figure 2) have proven to be feasible for products, such as halichondrin [70], avarol [61] and discodermolide [71], ex situ approaches have not yet been very successful, mostly due to the lack of scientific knowledge on sponge biology.…”
Section: Aquaculture Of Marine Invertebratesmentioning
confidence: 99%
“…Cell culture would present conditions that could be controlled and combined with the ability to engineer the metabolic network to improve yields. Currently this approach is limited by the difficulties in sustaining long-term cultures of either sponge cells or their associated bacteria (De Rosa et al, 2003;Grasela et al, 2011;Osinga et al, 2003;Rinkevich, 2011;Schippers et al, 2012). We simply do not know enough about the metabolism of sponges, or their bacterial symbionts, to establish and maintain long-term and sustainable cultures.…”
Section: Sponges Are Key Nutrient Cyclers and Producers Of Secondary mentioning
confidence: 99%
“…Reconstructing the amino acid synthesis pathways in A. queenslandica revealed that it has the same essential dietary amino acid requirements as other metazoans (section 5.4.3) (Payne & Loomis, 2006;Rose et al, 2003). This has implications for sponge cell culture where commercial mammalian cell culture media has been used (De Rosa et al, 2003;GarciaCamacho et al, 2006;Grasela et al, 2011;Zhang et al, 2008;Zhao et al, 2008). The inclusion off the essential amino acids for A. queenslandica in mammalian cell culture media indicates that the lack of developing a primary culture is not due to an amino acid deficiency and other metabolites may be essential nutrients.…”
Section: The Metabolic Network Of a Queenslandica And Aqs1mentioning
confidence: 99%